The forgotten role of absorption in music reward. Issue 1 (19th May 2022) - Cardona, Gemma; Ferreri, Laura; Lorenzo‐Seva, Urbano; Russo, Frank A.; Rodriguez‐Fornells, Antoni
Abstract: Interindividual differences in music‐related reward have been characterized as involving five main facets: musical seeking, emotion evocation, mood regulation, social reward, and sensory‐motor. An interesting concept related to how humans decode music as a rewarding experience is music transcendence or absorption (i.e., music‐driven states of complete immersion, including momentary loss of self‐consciousness or even time‐space disorientation). Here, we investigated the relation between previously characterized facets of music reward and individual differences in music absorption. A first sample of participants ( N  = 370) completed both the Barcelona Music Reward Questionnaire (BMRQ) and the Absorption in Music Scale (AIMS). Results showed that both constructs were highly interrelated ( r  = 0.78, p  < 0.001), indicating that higher music reward sensitivity is associated with a greater tendency to music‐related absorption states. In addition, four items from the AIMS were identified as suitable to be added to an extended version of the BMRQ (eBMRQ). A second sample ( N  = 550) completed the eBMRQ for a validation study. Exploratory and confirmatory factor analyses on the whole sample ( N  = 920) showed the reliable psychometric properties of the eBMRQ and suggested that taking into account an absorption facet could contribute to a better characterization of individual differences in the sensitivity to experience music‐related reward and pleasure. Abstract : The present research aims at understanding the relationship between transcendence or absorption states during music listening and individual differences in the susceptibility to experience reward from music. Overall, we showed that there is a close relationship between individual differences in the susceptibility to experience music‐related absorption states and in the ability to experience reward from music.